2002
DOI: 10.1142/s0218625x02003329
|View full text |Cite
|
Sign up to set email alerts
|

USXES AND OPTICAL PHENOMENA IN Si LOW-DIMENSIONAL STRUCTURES DEPENDENT ON MORPHOLOGY AND SILICON OXIDE COMPOSITION ON Si SURFACE

Abstract: It has been shown that the intensive and broad "red" photoluminescence band in porous silicon is a nonelementary one and could be decomposed on at least three elementary bands. Photoluminescence, ultrasoft X-ray emission spectroscopy, infrared absorption and atomic force microscopy methods were used to study the reasons for both luminescence band appearance in porous silicon photoluminescence spectra, prepared in different technological conditions. The mechanisms of radiative transition for both elementary ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Since the reconstruction of XANES spectra in this energy range can be due only to the change of the nearest neighboring for silicon atoms by oxygen ions the obtained results allow to assume that the result of oxidation of porSi surface does not respond to SiO 2 oxide. According to the data of X-ray emission and XPS measurements the surface oxide layer represents a mixture of the oxide SiO 2 and sub-oxide SiO x [7,9,13,14]. Therefore, it is possible to consider that XANES spectra of nanoporous silicon also indicate at the formation of sub-oxides SiO x , where x differs from 2, on the surface of por-Si.…”
Section: Xanes Resultsmentioning
confidence: 99%
“…Since the reconstruction of XANES spectra in this energy range can be due only to the change of the nearest neighboring for silicon atoms by oxygen ions the obtained results allow to assume that the result of oxidation of porSi surface does not respond to SiO 2 oxide. According to the data of X-ray emission and XPS measurements the surface oxide layer represents a mixture of the oxide SiO 2 and sub-oxide SiO x [7,9,13,14]. Therefore, it is possible to consider that XANES spectra of nanoporous silicon also indicate at the formation of sub-oxides SiO x , where x differs from 2, on the surface of por-Si.…”
Section: Xanes Resultsmentioning
confidence: 99%
“…The effect of a background appears in Raman spectrum is very well known for heavily disordered (or amorphous) Si crystals [13]. This implies that the etching process is accompanied by the amorphization of Si nano crystallite surface, as we have shown earlier [14]. Current voltage (I-V) characteristics at the reverse bias measured in the dark and at the light exposition are presented in Fig.…”
Section: Resultsmentioning
confidence: 55%
“…It was shown that mentioned above PL bands are connected with interface Si/SiOx oxide related defect luminescence. With increase of the etching current density the surface of PSi layer essentially oxidized and the composition of oxide changes from suboxide into dioxide [10][11][12]14]. The later is the reason the PL spectra changes and the PL band shifts into higher energy spectral range [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 630 nm is the most intense among the three bands, and can be attributed to electron-hole recombination in silicon nanocrystallites due to quantum-confinement behavior. The weak band at 700 nm, can be attributed to the interface defects between nanocrystalline Si and silicon oxide or suboxide, or due to quantum-confined NCs of large size (>2 nm) [112]. In order to explore the site-selective luminescence it is necessary to address which site is responsible for the observed luminescence.…”
Section: Xeol Of Si Nanocrystalsmentioning
confidence: 99%